2018
DOI: 10.3390/ijms19072127
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Dysfunctional and Healthy Mitochondria in Stroke Pathology and Its Treatment

Abstract: Stroke remains a major cause of death and disability in the United States and around the world. Solid safety and efficacy profiles of novel stroke therapeutics have been generated in the laboratory, but most failed in clinical trials. Investigations into the pathology and treatment of the disease remain a key research endeavor in advancing scientific understanding and clinical applications. In particular, cell-based regenerative medicine, specifically stem cell transplantation, may hold promise as a stroke the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 182 publications
0
11
0
Order By: Relevance
“…Mitochondria are the energy factory of cells, and mitochondrial impairment in the CNS induces neuronal injury and death, ultimately leading to neurological dysfunction. Therefore, maintaining neuronal mitochondrial function could be a promising therapeutic strategy for treating stroke 24 . Cannabinoid receptors are expressed in brain tissue, and activation of these receptors give rise to neuroprotection against brain IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the energy factory of cells, and mitochondrial impairment in the CNS induces neuronal injury and death, ultimately leading to neurological dysfunction. Therefore, maintaining neuronal mitochondrial function could be a promising therapeutic strategy for treating stroke 24 . Cannabinoid receptors are expressed in brain tissue, and activation of these receptors give rise to neuroprotection against brain IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, a DNA containing cellular organelle, plays an important role in producing adenosine triphosphate (ATP), maintaining redox balance, and regulating cellular apoptosis [6,17]. After brain ischemia, mitochondrial homeostasis is impaired in neurons [18], which constitutes a comprehensive of pathological process (Fig.…”
Section: Mitochondrial Dysfunctions After Brain Ischemiamentioning
confidence: 99%
“…Whereas earlier research mainly focused on mitochondrial bioenergetic roles, new studies have shown the importance of apoptotic signaling, mitochondrial biogenesis, and mitophagy in the development of cerebrovascular disease and stroke. Mitochondrial health is therefore essential for neurological survival and rehabilitation [ 198 , 199 ]. Reperfusion injury is another acute complication feared by medical doctors involving mitochondria and clinical outcomes [ 200 , 201 ].…”
Section: Traumatic and Ischemic Central Nervous System Injuriesmentioning
confidence: 99%